Risk factors for shoulder pain and injury in swimmers: A critical systematic review. Issue 4 (2nd October 2015) - Hill, Lee; Collins, Malcolm; Posthumus, Michael
Abstract: Swimming is one of the most popular recreational and competitive sporting activities. In the 2013/2014 swimming season, 9630 men and 12, 333 women were registered with the National Collegiate Athletics Association in the USA. The repetitive nature of the swimming stroke and demanding training programs of its athletes raises a number of concerns regarding incidence and severity of injuries that a swimmer might experience during a competitive season. A number of risk factors have previously been identified but the level of evidence from individual studies, as well as the level of certainty that these factors predispose a swimmer to pain and injury, to our knowledge has yet to be critically evaluated in a systematic review. Therefore, the primary objective of this review is to conduct a systematic review to critically assess the published evidence for risk factors that may predispose a swimmer to shoulder pain and injury. Three electronic databases, ScienceDirect, PubMed and SpringerLink, were searched using keywords "(Injury OR pain) AND (Swim*)" and "(Shoulder) AND (Swim*)". Based on the inclusion and exclusion criteria, 2731 unique titles were identified and were analyzed to a final 29 articles. Only articles with a level of evidence of I, II and III were included according to robust study design and data analysis. The level of certainty for each risk factor was determined. No studies were determined to have a high level of certainty, clinical joint laxity and instability, internal/external rotation, previous history of pain and injury and competitive level were determined to have a moderate level of certainty. All other risk factors were evaluated as having a low level of certainty. Although several risk factors were identified from the reviewed studies, prospective cohort studies, larger sample sizes, consistent and robust measures of risk should be employed in future research.